The investor's quotient : the psychology of successful investing in commodities and stocks - Bernstein, Jacob, 1946- (John Wiley and Sons, 1993)
My story. Many markets-many similarities. Psychology and the markets. Psychoanalytic theory-do childhood experiences affect behavior? Learning theory. The response sector. The consequences of behavior. The discovery process...